2012
DOI: 10.1371/journal.pone.0041079
|View full text |Cite
|
Sign up to set email alerts
|

Bacteroides uniformis CECT 7771 Ameliorates Metabolic and Immunological Dysfunction in Mice with High-Fat-Diet Induced Obesity

Abstract: BackgroundAssociations have been made between obesity and reduced intestinal numbers of members of the phylum Bacteroidetes, but there is no direct evidence of the role these bacteria play in obesity. Herein, the effects of Bacteroides uniformis CECT 7771 on obesity-related metabolic and immune alterations have been evaluated.Methods and FindingsAdult (6–8 week) male wild-type C57BL-6 mice were fed a standard diet or a high-fat-diet HFD to induce obesity, supplemented or not with B. uniformis CECT 7771 for sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
205
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(217 citation statements)
references
References 56 publications
(69 reference statements)
11
205
0
1
Order By: Relevance
“…This shift has significant effects on GH and sugar metabolism in these taxonomic groups. Species such as B. acidifaciens and B. uniformis ameliorate obesity by immunomodulation and improved host metabolism (Gauffin Cano et al, 2012; Yang et al, 2017). However, the mechanism for these effects is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This shift has significant effects on GH and sugar metabolism in these taxonomic groups. Species such as B. acidifaciens and B. uniformis ameliorate obesity by immunomodulation and improved host metabolism (Gauffin Cano et al, 2012; Yang et al, 2017). However, the mechanism for these effects is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration of the B. uniformis CECT 7771 strain ameliorated HFD-induced metabolic dysfunction in obese mice (62). Our group has recently reported that HFD-fed mice given B. acidifaciens for 10 weeks gained less fat mass and body weight than those given PBS alone (45).…”
Section: Symbionts In Metabolic Diseasesmentioning
confidence: 91%
“…Dosing of conventionally raised mice with cultures of B. uniformis [51], B. acidifaciens [52], or P. copri [29] resulted in improved glucose tolerance and insulin sensitivity compared to dosing with heat-killed cultures as controls. Authors of these studies speculate that microbial metabolites could be effectors of improved metabolism.…”
Section: Bacteroidetes and Metabolic Diseasementioning
confidence: 99%